Patterns of Neoplasm Among the Tribal and Non-Tribal Communities in Wayanad District of Kerala, India: A Hospital Based Cross-Sectional Study - Vinod Mohandas, Neeraj; George, Neethu; Vasudevan, Sanjeev; Dinesh, Avani; Mohandas, Vinod; Kulothungan, Karthikeyan; Britto Dharmaraj, Rock; Muniyapillai, Tamilarasan; Jeevagan, Abishek (National Journal of Community Medicine, 2024)
Background: The burden of neoplasms coupled with the inaccessibility to health services has always been a public health concern among the tribal population. The objective of the study was to determine the patterns of neoplasm and its associated factors among the tribal and non-tribal communities attending a primary care hospital in Wayanad, Kerala. Methodology: A record based cross-sectional study was conducted in a primary care hospital in Wayanad, Kerala. Data of patients who attended the hospital from January 2016 to December 2021 were collected from the procedure registry. The independent predictors of the community were identified using regression model (p value <0.05 was significant). Results: Among the 650 study participants, majority (85.3%) were females. The mean (±SD) age was 41.62 ± 15.26 years. Only 8.5% of the study participants had malignant lesions. Multivariable analysis revealed that the pre-malignant and malignant lesions were more among the tribals [AOR (95% CI) =3.31 (1.46-7.52)] with a female preponderance [AOR (95% CI) =1.99 (1.17-3.40)]. The other independent predictors of the community were neoplasms of gastrointestinal system [AOR (95% CI) =2.90 (1.04-8.04)] and age less than 20 years [AOR (95% CI) =2.42 (1.06-5.54)]. Conclusion: An increasing trend of malignancy and pre-malignancy is seen among the tribal communities.